The Life and Death of Industrial Languedoc, 1700-1920. - Johnson, Christopher H. (Oxford University Press, 1995)
This study of the rise and decline of industrialization in the Bas-Languedoc region of France uses a 200-year time-frame to examine the process of how and why a successful industrial region manufacturing woollens transformed itself into an agricultural, wine-growing area.